2012
DOI: 10.1017/s2045796012000637
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural/emotional problems in Brazilian children: findings from parents' reports on the Child Behavior Checklist

Abstract: Background. To compare Child Behavior Checklist (CBCL) findings for a large Brazilian general population sample with those for US children considering: (a) mean problem item ratings; (b) fit of the US-derived CBCL 8-syndrome model; (c) scale internal consistency measured by Cronbach's alphas; (d) effects of society, age, gender on CBCL problem scores; and (e) ability to discriminate referred from non-referred children. Methods. Parents of 1228 non-referred 6-to-11-year-olds from three different regions of Braz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
15

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 24 publications
1
13
0
15
Order By: Relevance
“…Gender patterns were comparable to those reported in other societies, but mean problem scores for non-referred Brazilian children were higher than those for USA children. These findings replicated those reported in international comparisons of CBCL 6/18 scores for 31societies, thereby providing support for the multicultural robustness of the CBCL 6/18 in Brazil (more details in Rocha et al, 2012).…”
Section: Instrumentssupporting
confidence: 82%
“…Gender patterns were comparable to those reported in other societies, but mean problem scores for non-referred Brazilian children were higher than those for USA children. These findings replicated those reported in international comparisons of CBCL 6/18 scores for 31societies, thereby providing support for the multicultural robustness of the CBCL 6/18 in Brazil (more details in Rocha et al, 2012).…”
Section: Instrumentssupporting
confidence: 82%
“…For each of the eight empirically derived (syndrome) scales (Anxious/Depressed, Withdrawn/Depressed, Somatic Complaints, Social Problems, Thought Problems, Attention Problems, Rule‐breaking Behaviour and Aggressive Behaviour) and three higher‐order factors (Internalising Problems, Externalising Problems and Total Problems) T‐scores were calculated from raw scores based on the American norms (Achenbach & Rescorla, ), as Brazilian norms were not available when the study was conducted. Confirmatory analysis indicated that the data for the Brazilian children in the norming sample showed an excellent fit to the US factor structure (Rocha et al , ). Based on the CBCL authors' guidelines (Achenbach & Rescorla, ), T‐scores <65 for the syndrome scales were considered typical, T‐scores between 65 and 69 were considered to be in the borderline range and T‐scores of 70 or above were considered to be in the clinical range.…”
Section: Methodsmentioning
confidence: 99%
“…Child Behavior Checklist -CBCL (Achenbach & Rescorla, 2001, Alpha de Cronbach 0,97 para consistência interna total da escala). Esse instrumento apresenta evidências preliminares de validade para a população brasileira (Rocha et al, 2013). Escala que avalia os problemas emocionais e de comportamento dos fi lhos composta de 138 itens, destinado aos pais/mães ou cuidadores.…”
Section: Amostraunclassified